2022
DOI: 10.3389/fmicb.2021.806902
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Antiviral Immune Responses in Severe Acute Respiratory Syndrome Coronavirus Infected Pregnant Mice

Abstract: Sex differences in immune responses had been reported to correlate with different symptoms and mortality in the disease course of coronavirus disease 2019 (COVID-19). However, whether severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection interferes with females’ fertility and causes different symptoms among pregnant and non-pregnant females remains unknown. Here, we examined the differences in viral loads, SARS-CoV-2-specific antibody titers, proinflammatory cytokines, and levels of T cell activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Infection with SARS-CoV-2 at the post-implantation stage did not induce a significant difference in pregnancy outcomes compared to the control group. This result is similar to previously published findings that state that embryo resorption did not occur in infected mice after E4.5 [ 26 ]. Viral RNA was not detected in the female reproductive tract, indicating that the virus cannot infect the reproductive tract or the fetus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Infection with SARS-CoV-2 at the post-implantation stage did not induce a significant difference in pregnancy outcomes compared to the control group. This result is similar to previously published findings that state that embryo resorption did not occur in infected mice after E4.5 [ 26 ]. Viral RNA was not detected in the female reproductive tract, indicating that the virus cannot infect the reproductive tract or the fetus.…”
Section: Discussionsupporting
confidence: 93%
“…K18-hACE2 transgenic mice are the most sensitive to SARS-CoV-2 and can model non-severe and severe SARS-CoV-2 affected patients in many animal models [ 25 ]. Studies using K18-hACE2 transgenic mice revealed the expression of hACE2 mRNA in the lungs, brain, kidneys, and small intestine [ 25 , 26 ]. In addition, it has been discovered that the neuro-invasion of SARS-CoV-2 is dependent on hACE2 expression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data and studies in pregnant mice demonstrate pregnancy is a risk factor for severe COVID-19, and vaccination has been associated with improved outcomes. 48,49 In the search for a universal influenza vaccine, these findings highlight the functionality of maternal antibodies elicited via distinct vaccine delivery systems and are vital to refine vaccine development pipelines for this high-risk group. Our results are in alignment with recent advances such as Pfizer's maternal respiratory syncytial virus (RSV) vaccine.…”
Section: Discussion (1256)mentioning
confidence: 99%
“…This could be addressed with single cell RNA sequencing studies in the future. Fifth, despite upregulated innate immune surveillance, other facets of infection, such as viral clearance and activation of adaptive immunity could be adversely impacted with pregnancy as was recently shown in pregnant transgenic hACE2-chimera female mice [ 54 ], or by sex hormones per se [ 55 57 ]. More importantly, we only capture the baseline state of innate immune gene expression and, therefore, are unable to comment on whether such enhanced expression results in increased ability to respond to viral challenge.…”
Section: Discussionmentioning
confidence: 99%